Bias distribution of Pristionchus nematodes found in Cat Tien and Cuc Phuong National Parks, Vietnam: Pristionchus nematodes - Son, Le Tho; Nhu Ngoc, Nguyen; Quang Trung, Do (Vietnam Journal of Biotechnology, 2023)
The Pristionchus nematodes are distributed in many places worldwide, so they should be diverse in many aspects of biology. The most updated species, P. pacificus, has many differences from and similarities to the standard model organism, Caenorhabditis elegans, and become a parallel but complementary laboratory model for research in genetics, diversity, and evolution. It therefore acquires the demonstration of wild-type isolates of the Pristionchus species in various habitats. In the survey of the soil nematodes, we collected vegetation samples from forests and used them to isolate nematodes. The nematodes were raised in the laboratory to determine their species. In this research, we report the finding of numerous strains within the genus Pristionchus. By comparing the 18S rDNA sequences as an advanced barcode for the classification of free-living nematodes, we identified them in two different species (P. pacificus and P. chinensis) and predicted one new Pristionchus species. Of them, P. pacificus strains are dominant, more in the north and less in the south of Vietnam, and they likely evolved independently over time. The P. chinensis and new Pristionchus sp. were less distributed and probably found by chance. This result extends the global diversity of the nematode genus Pristionchus, facilitating future studies of evolutionary nematodes.